Os desafios do ensino de Filosofia em escolas públicas da cidade de Manaus: perspectivas, tendências e práticas no Ensino Médio - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The central question of this dissertation is to present a research on the teaching and learning of Philosophy in public schools. The present study was anchored in the general objective of knowing the challenges of Philosophy teaching in public schools in the city of Manaus, aiming to understand the perspectives, trends and practices of this curricular component in High School. The study focuses on investigating the main issues that are challenging for the teaching of Philosophy in the local context, thus providing a critical review of the role of the public school in the critical-reflective development of the student, a reassessment of what the school has already built the adopted procedures, questioning what is considered essential and trying to rethink the social function of the school, its meaning and role in today's society. The research was developed with the help of the following instruments of data collection: directed interview with teachers who act as Philosophy teachers in public high school in the city of Manaus; questionnaire with open questions for students regularly enrolled in the Undergraduate Program in Philosophy at the Federal University of Amazonas, who act as scholarship recipients of the Institutional Scholarship Program (PIBID) and another one directed to the 3rd year high school students regularly enrolled and attending the Philosophy classes at a public school in the city of Manaus. The collected data received a qualitative approach and were based on the phenomenological method. With the data collected, we can see that, as a reflection of his recent return to the school curriculum, Philosophy teaching faces many challenges. These are issues such as overloading of class time, making the teacher work with many classes in a few hours of class a week. Another issue, is the notorious difficulty that students demonstrate in mastering the writing, reading and interpretation of philosophical texts.
Keywords: Ensino de Filosofia; Escola Pública; Ensino Médio; CIÊNCIAS HUMANAS: EDUCAÇÃO: ENSINO-APRENDIZAGEM